Current Population Survey, February 1999: Contingent Work Supplement ([Verlag nicht ermittelbar], 2000)
This collection provides data on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 15 years old and over. Also shown are personal characteristics such as age, sex, race, marital status, veteran status, household relationship, educational background, and Hispanic origin. The Contingent Work Supplement questions were asked of all household members aged 15 years or older who had jobs during the reference week and worked for pay or profit or who did not have jobs during the reference week but looked for work during the last year and were available for work during the reference week. The supplement data include information on contingent or temporary work performed without the expectation of continuing employment from an employer. Also included is information about each worker's expectation of continuing employment, satisfaction with his or her current employment arrangement, current job history, transition into the current employment arrangement, search for other employment, employee benefits, and earnings.